Sosialisasi Pemanfaatan Tiktok Dalam Media Pembelajaran Di Mis Darul Mustofa - mahmudah, muhlisatul; Irawati, Tri Novita; Reni Pitasari, Mely Agustin; Arifannah, Dwi Septy; Wahyuni, Linda Sri; Khoirunnisa, Najhan (PENDIMAS: Jurnal Pengabdian Masyarakat, 2025)
21st-century education faces challenges in developing students' critical thinking skills, collaboration, and digital literacy. One of the challenges is low student learning outcomes at the elementary school level, caused by a lack of diverse learning media. TikTok, as a popular social media platform, has great potential for use in learning. The outreach activities conducted at MIS Darul Mustofa aimed to provide students, teachers, and principals with an understanding of the use of TikTok as an effective and responsible learning tool. The activities demonstrated student enthusiasm and increased awareness of TikTok's benefits in learning. Teachers recognized TikTok as an engaging and interactive medium, while the principal was inspired to encourage the use of digital technology in schools. These activities had a positive impact on improving the quality of learning and student engagement